Tunable surface acoustic wave device using semiconducting MgZnO and piezoelectric NiZnO dual-layer structure on glass. (25th July 2018) - Li, Rui; Li, Guangyuan; Hong, Wen-Chiang; Reyes, Pavel I; Tang, Ke; Yang, Keyang; Wang, Szu-Ying; Ye, Hongfei; Li, Yuxuan; Zhang, Lihua; Kisslinger, Kim; Lu, Yicheng
Abstract: Tunable surface acoustic wave (SAW) devices have attracted considerable interests due to its applications in emerging fields, such as secured wireless communication, adaptive signal processing, and smart sensing systems. We report a dual-input-voltage-controlled tunable SAW built on glass, which uses a ZnO-based dual-layer structure consisting of a piezoelectric Ni-doped ZnO (NZO) and semiconducting Mg-doped ZnO (MZO). The interdigital (IDT) electrodes are buried in the piezoelectric NZO layer to form the delay line for SAW propagation, while the semiconductor MZO layer serves as the channel of a thin film transistor (TFT) to modulate the conductivity. Results show the interface between MZO channel and SiO2 gate dielectric layer of the TFT significantly impacts on SAW tuning performances due to Zn diffusion from MZO into SiO2 . The TFT-SAW device using an ultra-thin MgO layer as interface modification enables SAW frequency tuning of 0.53% under solely V gs control with 0–12 V. The required voltage range is significantly reduced compared regular MZO-NZO TFT-SAW counterpart (Δ f / f c ∼ 0.25%; V gs −30 to −14 V) without interface modification. With additional control of V ds, the SAW frequency tunability is further expanded from 0.46% to 0.63%. This dual-input voltage-controlled frequency tuning device on glass is promising for low-voltage, low-cost portable smart sensors and voltage-controlled reconfigurable radio-frequency identification tags.